A case study on use frequency and perceived usefulness of vocabulary learning strategies used by Chinese EFL learners - Chen, Man (Frontiers in Education, 2025)
This study investigates the vocabulary learning strategies employed by senior high school students in Beijing, addressing a gap in research focusing predominantly on adult or college learners. Utilizing Schmitt's (1997) classification, the research explores strategy use frequency and perceived effectiveness among a sample of 136 EFL learners, considering the influence of language proficiency on strategy selection. It is discovered that students frequently used determination, memory, and cognitive strategies (especially word list, pronunciation, and repetition); they also perceived determination, cognitive, and meta-cognitive strategies (including word list, pronunciation, and repetition) as most useful, with notable similarities between frequently used and perceived as useful VLS. The findings of this study can provide targeted pedagogical guidance for English vocabulary teaching in senior high schools, help teachers optimize strategy instruction, and further promote students’ autonomy and efficiency in vocabulary learning.